PENGARUH PENDEKATAN SAINTIFIK PADA MATERI BERNYANYI SOLO DITINJAU DARI ASPEK KOGNITIF - Ramadhan, Mohammad Ilham; Heldisari, Hana Permata; Pratama, Ujang Nendra (Universitas Tanjungpura, 2024)
Learning outcomes are changes in behavior that involve affective, cognitive, and psychomotor. The scientific approach has stages, namely observing, questioning, gathering information and communicating. The importance of a learner-centered approach and emphasizes the ability to think to improve learning outcomes in the cognitive aspects of cultural arts (music) material. This study aims to determine the effect of the scientific approach on the cognitive aspects of solo vocal singing material. The place used in this research is SMPN 14 Yogyakarta. The research method used is quantitative research method with experimental research type. The experimental research design used was One Group Pretest-posttest Design. Sampling using Cluster Sampling technique with a total of 57 samples. The research instrument is a learning outcome test. Data analysis used in this study using paired t-test. The results of the Paired t-test analysis obtained the value of t (12.54 ) t table (2.00) and the significance value (0,00) 0.05, so that Ha there is an influence of the scientific approach on the learning outcomes of vocal solo material significantly in class 9th at SMP N 14 Yogyakarta is accepted. The results of the pretest and posttest showed an increase in the average score of 41.3%. Based on the results of this analysis, the scientific approach has an effect on the learning outcomes of cognitive aspects of solo vocal singing material significantly on grade IX students at SMP N14 Yogyakarta.